\({\lim_{x\to0}}\)\({\lim_{y\to0}}\)xy\(\frac{x^2-y^2}{x^2+y^2}\)=
______
______
举一反三
- \({\lim_{x\to0}}\)\({\lim_{y\to0}}\)\(\frac{tan(x^2+y^2)}{x^2+y^2}\)= <br/>______
- \({\lim_{x\to0}}\)\({\lim_{y\to0}}\)\(\frac{sin(x^2+y^2)}{x^2+y^2}\)= <br/>______
- \({\lim_{x\to0}}\)\({\lim_{y\to0}}\)\(\frac{xy}{x^2+y^2}\)= A: 0 B: 1 C: 1/2 D: 不存在
- \({\lim_{x\to0}}\)\({\lim_{y\to0}}\)\(\frac{xy}{(x^2+y^2)^2}\)= A: 0 B: 1 C: -1 D: 不存在
- \({\lim_{x\to0}}\)\({\lim_{y\to0}}\)\(\frac{x^2+y^2+1}{x^2-y^2}\) A: 0 B: 1 C: -1 D: 不存在